Efficacy of antibacterial agents combined with erbium laser and photodynamic therapy in reducing titanium biofilm vitality: an in vitro study - Jing Wang; Tengyu Geng; Yuzhuo Wang; Changyong Yuan; Penglai Wang (BMC, 2023)
Abstract Background and objective The emergence of peri-implant diseases has prompted various methods for decontaminating the implant surface. This study compared the effectiveness of three different approaches, chlorhexidine digluconate (CHX) combined with erbium-doped yttrium-aluminum-garnet (Er:YAG) laser, photodynamic therapy (PDT), and CHX only, for reducing biofilm vitality from implant-like titanium surfaces. Study design/Materials and methods The study involved eight volunteers, each receiving a custom mouth device containing eight titanium discs. The volunteers were requested to wear the device for 72 h for biofilm development. Fluorescence microscopy was used to evaluate the remaining biofilm with a two-component nucleic acid dye kit. The vital residual biofilm was quantified as a percentage of the surface area using image analysis software. Sixty-four titanium discs were assigned randomly to one of four treatment groups. Results The percentage of titanium disc area covered by vital residual biofilm was 43.9% (7.7%), 32.2% (7.0%), 56.6% (3.6%), and 73.2% (7.8%) in the PDT, Er:YAG, CHX, and control groups, respectively (mean (SD)). Compared to the control group, the treatment groups showed significant differences in the area covered by residual biofilm (P < 0.001). CHX combined with Er:YAG laser treatment was superior to CHX combined with PDT, and CHX only was better than the control. Conclusion Within the current in vitro model's limitations, CHX combined with Er:YAG laser treatment is a valid method to reduce biofilm vitality on titanium discs.